2022
DOI: 10.3847/1538-4357/ac616f
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of the Cetus Stream Unveiled from the Fusion of STREAMFINDER and StarGO

Abstract: We combine the power of two stream-searching tools, STREAMFINDER and StarGO applied to the Gaia EDR3 data, to detect stellar debris belonging to the Cetus stream system that forms a complex, nearly polar structure around the Milky Way. In this work, we find the southern extensions of the northern Cetus stream as the Palca stream and a new southern stream, which overlap on the sky but have different distances. These two stream wraps extend over more than ∼100° on the sky (−60° < δ < +40°). The current N-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…Using the same line of reasoning as above, we can use our models to identify substructures which are not associated to the GSE merger event. For example, besides Heracles (see Section 5.3), we argue that LMS-1/Wukong (Naidu et al 2020;Yuan et al 2020b) and Cetus (Newberg et al 2009;Yuan et al 2019Yuan et al , 2022) also most likely have distinct progenitors other than the GSE. Malhan et al (2022) showed that both substructures have J z ≈ 2000 kpc km s −1 , meaning they have large vertical excursions.…”
Section: Other Substructures: a Cautionary Approachmentioning
confidence: 78%
“…Using the same line of reasoning as above, we can use our models to identify substructures which are not associated to the GSE merger event. For example, besides Heracles (see Section 5.3), we argue that LMS-1/Wukong (Naidu et al 2020;Yuan et al 2020b) and Cetus (Newberg et al 2009;Yuan et al 2019Yuan et al , 2022) also most likely have distinct progenitors other than the GSE. Malhan et al (2022) showed that both substructures have J z ≈ 2000 kpc km s −1 , meaning they have large vertical excursions.…”
Section: Other Substructures: a Cautionary Approachmentioning
confidence: 78%
“…Our prior expectation was that the majority of pairs would reside in known streams, since stellar streams span tens of degrees on the sky and have a significantly enhanced probability of hosting comoving stars within a few degrees of each other. Groups #1 and #2 could securely be associated with the Cetus stream based on their sky position and kinematics (Newberg et al 2009;Yuan et al 2022). Group #3 was likewise strongly associated with the Orphan stream (Belokurov et al 2007a;Koposov et al 2019).…”
Section: Search For Structures In H3mentioning
confidence: 91%
“…14 ). After verification with known structures, it became apparent that this structure corresponds to the Pisces-T riangulum (Psc-T ri) that, at a distance of ∼ 30 kpc (Bonaca, Geha & Kalli v ayalil 2012 ;Martin et al 2013 ;Yuan et al 2022 ), is located at the very edge of the STREAMFINDER exploration. Martin et al ( 2013 ) determine an average metallicity for this stream from 11 stars and find [Fe/H] −2.2, which is in very good agreement with our measurement using Pristine and further confirms that the few stars we identify in the STREAMFINDER sample belong to Psc-Tri.…”
Section: Pisces-triangulummentioning
confidence: 95%